Time to treatment benefit for adult patients with Fabry disease receiving agalsidase β: data from the Fabry Registry - Ortiz, Alberto; Abiose, Ademola; Bichet, Daniel G; Cabrera, Gustavo; Charrow, Joel; Germain, Dominique P; Hopkin, Robert J; Jovanovic, Ana; Linhart, Aleš; Maruti, Sonia S; Mauer, Michael; Oliveira, João P; et al. (Journal of medical genetics, 2016)
BACKGROUND: Agalsidase β is a form of enzyme replacement therapy for Fabry disease, a genetic disorder characterised by low α-galactosidase A activity, accumulation of glycosphingolipids and life-threatening cardiovascular, renal and cerebrovascular events. In clinical trials, agalsidase β cleared glycolipid deposits from endothelial cells within 6 months; clearance from other cell types required sustained treatment. We hypothesised that there might be a 'lag time' to clinical benefit after initiating agalsidase β treatment, and analysed the incidence of severe clinical events over time in patients receiving agalsidase β. METHODS: The incidence of severe clinical events (renal failure, cardiac events, stroke, death) was studied in 1044 adult patients (641 men, 403 women) enrolled in the Fabry Registry who received agalsidase β (average dose 1 mg/kg every 2 weeks) for up to 5 years. RESULTS: The incidence of all severe clinical events was 111 per 1000 person-years (95% CI 84 to 145) during the first 6 months. After 6 months, the incidence decreased and remained stable within the range of 40-58 events per 1000 patient-years. The largest decrease in incidence rates was among male patients and those aged ≥40 years when agalsidase β was initiated. CONCLUSIONS: Contrary to the expected increased incidence of severe clinical events with time, adult patients with Fabry disease had decreased incidence of severe clinical events after 6 months treatment with agalsidase β 1 mg/kg every 2 weeks. TRIAL REGISTRATION NUMBER: NCT00196742.
Keywords: Registries; glykolipidy; Humans; lidé středního věku; Getting Research into Practice; registrace; Cardiovascular Medicine; Female; dospělí; výsledek terapie; alfa-galaktosidasa; Glycolipids; Time-to-Treatment; lidé; enzymová substituční terapie; Fabryho nemoc; Adult; čas zasáhnout při rozvinutí nemoci; Isoenzymes; ženské pohlaví; alpha-Galactosidase; Male; izoenzymy; Middle Aged; incidence; Incidence; Treatment Outcome; Enzyme Replacement Therapy; mužské pohlaví; Fabry Disease; Clinical genetics